Exploring Barriers in implementing Agile Supply Chain in Healthcare: An ISM & MICMAC Method - Mangesh A.Ahire, Dr.S.B.Rane, Dr.S.J.Gorane (International Journal of Advanced Science and Technology, 2020)
The purpose of this paper is to analyze the interaction among the barriers in the successful implementation of agile supply chain management (ASCM) in healthcare and to develop the managerial implications/guidelines for practitioners in healthcare organizations. Interpretative Structural Modelling (ISM) and MICMAC analysis are used as tools in the research methodology. This research work provides managerial implications/guidelines for practitioners for successful agile scm implementation in healthcare organizations. Hence the quick response and consequently fast service will be highly beneficial to society. First, it provides a hierarchical structure to illustrate the driving barriers and dependent barriers. Second, it ranks the barriers based on their inﬂuence on healthcare organizations. To achieve the above objectives, fourteen barriers of implementing agile SCM in healthcare organizations have been identiﬁed through an extensive literature survey followed by an expert interview to know the interactions and transitivity between the barriers and ﬁnally an analysis of the interrelationship using ISM. The results suggest that lack of organization structure and lack of top management support are the most crucial barriers for implementing agile SCM in the healthcare organization. This study is an attempt to shed light on those aspects and highlights the implication of interrelationship among agility-related barriers. The study underlines that having a less authoritative and employee-friendly organization is extremely crucial for the agile performance of a healthcare organization. Apart from this, a flexible workforce, training availability and implementation of employee and patient suggestions foster the agile capability of the organization. This study provides healthcare managers and policymakers with concrete guidance to improve system performance by adopting agile practices and opens a new area for service supply chain management research. Finally, limitations and scope of future research work pathways have been present to continue the current work.